2012
DOI: 10.1016/j.immuni.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Foxp3+ T Cells Reflects Promiscuous Foxp3 Expression in Conventional T Cells but Not Reprogramming of Regulatory T Cells

Abstract: The emerging notion of environment-induced reprogramming of Foxp3(+) regulatory T (Treg) cells into helper T (Th) cells remains controversial. By genetic fate mapping or adoptive transfers, we have identified a minor population of nonregulatory Foxp3(+) T cells exhibiting promiscuous and transient Foxp3 expression, which gave rise to Foxp3(-) ("exFoxp3") Th cells and selectively accumulated in inflammatory cytokine milieus or in lymphopenic environments including those in early ontogeny. In contrast, Treg cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
619
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 527 publications
(657 citation statements)
references
References 49 publications
32
619
2
4
Order By: Relevance
“…Normalized expression values Foxp3 expression in Tregs. [36][37][38] To determine the methylation status of the TSDR in Foxp3 þ RORgt þ T cells, we purified cells from spleen, LNs (pool of pLNs and mLNs), and colonic LP of Foxp3 RFP RORgt GFP mice and compared the TSDR methylation status to that of RORgt þ T cells, Foxp3 þ Tregs, and Foxp3 À RORgt À T cells isolated from the same organs. As shown in …”
Section: Resultsmentioning
confidence: 99%
“…Normalized expression values Foxp3 expression in Tregs. [36][37][38] To determine the methylation status of the TSDR in Foxp3 þ RORgt þ T cells, we purified cells from spleen, LNs (pool of pLNs and mLNs), and colonic LP of Foxp3 RFP RORgt GFP mice and compared the TSDR methylation status to that of RORgt þ T cells, Foxp3 þ Tregs, and Foxp3 À RORgt À T cells isolated from the same organs. As shown in …”
Section: Resultsmentioning
confidence: 99%
“…In our study, we considered FOXP3-positive cells to be regulatory T cells, as FOXP3 is considered to be a specific marker of regulatory T cells, although a minor amount of effector T cells can exhibit transient expression of FOXP3. [12][13][14] It has been suggested that T helper 2 and regulatory T cells are most important in the pathogenesis of IgG4-related disease. Although we did find that the number of FOXP3-positive regulatory T cells was significantly increased in IgG4-related disease in our study, we did not find any evidence that the FOXP3-positive regulatory T cells produced regulatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Occupancy by specific transcription factors at each of these loci is now characterised, and this includes AP1 and NFAT at CNS1,59 Runx1 and CBFβ at CNS264 and cREl at CNS3 63. The observation that naïve human CD4+ T cells induce FOXP3 upon activation,65, 66, 67 and that in the presence of TGFβ and all‐trans retinoic acid (ATRA)63 the expression of FOXP3 is stabilised to some degree, was defined transcriptionally by the finding that the activation‐induced expression of FOXP3 results from partial but not complete demethylation of the FOXP3 locus in iTreg 37. This suggests that the relative methylation state of the FOXP3 regulatory elements encoded by CNS1, 2 and 3 are an axis for Treg plasticity.…”
Section: Foxp3 Epigenetic Regulationmentioning
confidence: 99%